8-4n=6n+2

Simple and best practice solution for 8-4n=6n+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-4n=6n+2 equation:


Simplifying
8 + -4n = 6n + 2

Reorder the terms:
8 + -4n = 2 + 6n

Solving
8 + -4n = 2 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
8 + -4n + -6n = 2 + 6n + -6n

Combine like terms: -4n + -6n = -10n
8 + -10n = 2 + 6n + -6n

Combine like terms: 6n + -6n = 0
8 + -10n = 2 + 0
8 + -10n = 2

Add '-8' to each side of the equation.
8 + -8 + -10n = 2 + -8

Combine like terms: 8 + -8 = 0
0 + -10n = 2 + -8
-10n = 2 + -8

Combine like terms: 2 + -8 = -6
-10n = -6

Divide each side by '-10'.
n = 0.6

Simplifying
n = 0.6

See similar equations:

| -3y+9=-4y+3 | | 20/100= | | -10=-7+h | | -2x^3-2x^2=-40x | | 6x-6=9x-36 | | 20.2217(4.6666p-.25)=91.3611 | | 6x-6=9x-20 | | 6/10= | | .60= | | 20=-5x+2y | | 8-4n=6n | | 11x+16=2x+7 | | 37/50= | | 6z+24=6(z+4) | | 96=-4(6x-6) | | -3(3b+3)+(10b-2)=0 | | 4(3x+2)=2(6x+4) | | 45=x+34 | | p=32.50-4d+3.50 | | 27/50= | | 16x^4-81y^4=0 | | 4.8q-4.5-5.2q=-1.4q-2.2 | | K+4=11 | | 23/100= | | -6(3b+2)+(19b-2)=0 | | x-19=-2 | | 32.50=4d-2p-3.50 | | logx=-2 | | 4.8q-5.1-5.5q=-1.7q-5.1 | | 3x^3-27x^2=-24x | | y=15x^2-19x-8 | | 50+35.50x=653.50 |

Equations solver categories